Segmental Thoracic Spinal Anesthesia (TSA) for Open Reduction with Internal Fixation (ORIF) Surgery in Right Humeral Fracture Patients: A Case Report - Imam Ghozali; Natalia Danayati (Medula, 2023)
General anesthesia is used in most surgeries, but there has disadvantages, such as drug side effects and a long recovery. Spinal anesthesia such as TSA is starting to get attention and become an alternative option to reduce adverse effects and more effective. This case report, a 33-year-old woman diagnosed complete closed fracture of the 1/3 proximal right humerus underwent Open Reduction and Internal Fixation (ORIF) surgery with segmental thoracic Spinal Anesthesia (TSA). The patient presented with ASA II with mild electrolyte imbalance. Thoracic spinal anesthesia with a paramedian approach at the level of T4-5 vertebrae using a regimen levobupivacaine 5 mg. The adjuvants used were dexmedetomidine 5 mcg, ketamine 5 mg, and fentanyl 25 mcg. Intraoperative and postoperative monitoring of the patient's condition was stable, pain control was good, and no postoperative complications such as headache, nausea and vomiting. Thoracic segmental spinal anesthesia has several advantages such as the need for lower doses of anesthetic drugs and relatively safer than lumbar spinal anesthesia, good pain control, faster recovery, and can avoid the side effects of general anesthesia, so that TSA can be an alternative technical choice for anesthesia.